A randomized controlled trial of the effectiveness of “chest pain evaluation at emergency room” (cheer) protocol in the ed of HUSM: a model for Malaysian emergency departments - Bolong @ Darwis, Mohammad Firdaus @ Mohd (2020)
Background Management of low risk chest pain in adults is a problem in emergency department in Malaysia. Traditional use of CK/CKMB ratio among others has been used to manage patients presenting with low risk chest pain in Malaysia. Sometimes patients are admitted to the medical ward for observation due to the ambiguity of management of low risk chest pain thus creating overcrowding in ED or unnecessary referral and admission to the medical wards, which will occupy beds and worsen backlog of admission Methods This prospective randomised control trial included 53 patients with low risk chest pain admitted to Emergency department in Hospital USM. Patients were randomised to either a standard care arm for chest pain treatment according to current HUSM guideline or CHEER (Chest Pain Evaluation in Emergency Room) protocol arm which involves 8 hours observation with serial ECG and Troponin test. Patients information such as age, chest pain characteristics, demography, ECG findings, HEART and TIMI score were calculated during the stay. Patients were followed up after 6 weeks and 6 months to determine prevalence of Major Adverse Cardiac Event, Readmission to ED for chest pain, and their length of stay in hospital and rate of early discharge from ED. Results Study shows that CHEER protocol has overall shorter length of stay at ED or hospital and has higher early discharge rate compared to standard care. There is Background Management of low risk chest pain in adults is a problem in emergency department in Malaysia. Traditional use of CK/CKMB ratio among others has been used to manage patients presenting with low risk chest pain in Malaysia. Sometimes patients are admitted to the medical ward for observation due to the ambiguity of management of low risk chest pain thus creating overcrowding in ED or unnecessary referral and admission to the medical wards, which will occupy beds and worsen backlog of admission Methods This prospective randomised control trial included 53 patients with low risk chest pain admitted to Emergency department in Hospital USM. Patients were randomised to either a standard care arm for chest pain treatment according to current HUSM guideline or CHEER (Chest Pain Evaluation in Emergency Room) protocol arm which involves 8 hours observation with serial ECG and Troponin test. Patients information such as age, chest pain characteristics, demography, ECG findings, HEART and TIMI score were calculated during the stay. Patients were followed up after 6 weeks and 6 months to determine prevalence of Major Adverse Cardiac Event, Readmission to ED for chest pain, and their length of stay in hospital and rate of early discharge from ED. Results Study shows that CHEER protocol has overall shorter length of stay at ED or hospital and has higher early discharge rate compared to standard care. There is